Social Carrying Capacity as A Planning Tool for Sustainable Tourism: A Case of Pangkor Island, Perak, Malaysia - Mohamad Pirdaus Yusoh; Normah Abdul Latip; Nurhazliyana Hanafi; Ang, Kean Hua; Zulayti Zakaria; Mohamad Ikhram Mohamad Ridzuan (Malaysia Institute of Planners, 2023)
Tourism can drive economic growth and development in destinations, but unchecked growth can have negative impacts on local communities and the environment. To ensure that tourism is sustainable and does not cause harm, social carrying capacity (SCC) has become a useful planning tool. SCC refers to the maximum number of tourists that a destination can accommodate without exceeding the capacity of local resources, infrastructure, and services. This study aims to identify the level of crowding on public holidays at Pangkor Island and the acceptance levels of tourists and the local community regarding tourism. A quantitative methodology was used, involving 96 international tourists, 332 domestic tourists, and 387 members of the local community. The results indicate that the level of crowding on public holidays at Pangkor Island is still within acceptable limits. The barometer showed that international tourist respondents rated the level of crowding as excellent (green colour), while domestic tourist respondents rated it as acceptable (yellow colour). Local community respondents also rated the level of crowding as high but still acceptable (green colour). This study concludes that the Social Carrying Capacity at Pangkor Island is still good, and it is important to maintain it to achieve sustainable tourism. By managing tourism growth and ensuring that the number of tourists does not exceed the SCC, destinations can reap the economic benefits of tourism while preserving the natural and cultural heritage of the area and protecting the well-being of the local community.